As expressões de choro dos bebês em uma escola municipal de educação infantil de Belo Horizonte - Fernanda Pedrosa Coutinho Marques (2019)
This work describes and analyses the expressions of the crying of babies among themselves, with their teachers and with the room support assistant at a Child Education Municipal School (EMEI) in Belo Horizonte/MG. Qualitative research was held in a class of 12 babies aged up to 1 year and 6 months old, four teachers and one support assistant, for about four months. Data were obtained through field diary records and films. We also analyzed documents on the group of babies, their families, and conducted semi-structured interviews with the teachers and with the room support assistant. The theoretical framework articulated studies in the Sociology of Childhood, more specifically, of Historical-Cultural Psychology thus developed by Vygotsky and Wallon, and studies on Early Childhood Education that claim to the agency and the potential of the babies in their interactions established with others, particularly in collective spaces. The results obtained showed that, in relation to the organization of times and spaces for the group of babies, the school offers a good structure. However, there were not enough objects and materials arranged for the babies, except when there was some specific activity scheduled for them. The babies spent most of the day in indoors activities and they were only outside for short periods of time. It was in this environment where we noticed the highest number of scenes of babies crying. The analysis of the interviews carried out with teachers and room assistants indicated that they understood crying as a form of communication by the babies, mainly associated with physical and biological needs as well as with the wish to have something, named by the participants as manha, birra (tantrum) or pirraça. Despite of realizing that crying is a way of communication by babies and, most of the time, to respond to it appropriately, we generally perceive, in teachers speeches as well as the assistant, a lack of conscience towards the theme of emotions and affectivity which, in turn, is related to the possibility of practices neglecting important aspects of support to infants psychic development. By means of the analyses of the footage and records on field diary it was possible to have indications of four types of crying: 1) Crying as a sign of attempted communication with others; 2) Crying as infants manifestation of physical and biological needs; 3) Crying as a manifestation of the desire towards a relationship with teachers and the room support assistant; and 4) Crying as an expression of anger and frustration. It was also evidenced that, when babies cry, teachers usually answer with the following actions: approaching and talking to the babies; by checking their physical and biological needs; keeping or offering them some toy or object; and, somehow, ignoring the crying. The results of the research help to enhance understanding that it is essential that teachers be able to reflect on their own work so that they can evaluate ways of acting and be in the interaction they establish with the infants and to have different forms to carry out, in a more systematic practice, the support the infants full development.